Analysis of the subjective experience of suffering in the psychodynamic work clinic - Velásquez, Nestor Raúl Porras (Nusantara Journal of Behavioral and Social Science, 2024)
This study aims to investigate and deeply understand the subjective experience of suffering within the psychodynamic context of work, focusing particularly on the psychological and emotional aspects involved. Through qualitative analysis, this research delves into how individuals interpret and experience suffering in the workplace, considering the psychodynamic variables that influence their perceptions and reactions. This provides valuable insights into the internal dynamics of work-related suffering, as well as how these factors impact the psychological well-being of employees. Furthermore, the study explores how these findings can be applied in work intervention practices. By understanding the nuances of the subjective experience of suffering, practitioners can develop more effective and empathetic strategies to support employees facing psychological challenges in the workplace. This opens possibilities for interventions that are more tailored and responsive to the unique needs of individuals